A circulating TH2 cytokines profile predicts survival in patients with resectable pancreatic adenocarcinoma. (2nd September 2017) - Piro, Geny; Simionato, Francesca; Carbone, Carmine; Frizziero, Melissa; Malleo, Giuseppe; Zanini, Silvia; Casolino, Raffaella; Santoro, Raffaela; Mina, Maria Mihaela; Zecchetto, Camilla; Merz, Valeria; Scarpa, Aldo; et al.
ABSTRACT: Surgery is the only potentially curative option for patients with pancreatic ductal adenocarcinoma (PDAC), but metastatic relapse remains common. We hypothesized that the expression levels of inflammatory cytokines could predict recurrence of PDAC, thus allowing to select patients who most likely could benefit from surgical resection. We prospectively collected plasma at diagnosis from 287 patients with pancreatic resectable neoplasms. The expression levels of 23 cytokines were measured in 90 patients with PDAC by using a multiplex analyte profiling assay. Levels higher than cutoff identified of the TH 2 cytokines interleukin (IL)4, IL5, IL6 of macrophage inflammatory protein (MIP)1α, granulocyte-macrophage colony-stimulating factor (GM-CSF), and monocyte chemoattractant protein (MCP)1, and of IL17α, IFNγ-induced protein (IP)10, and IL1b were significantly associated with a shorter median OS. In particular, levels of IL4 and IP10 higher than cutoff identified, and level of TH 1 cytokines TNFα and INFγ, and of IL9 and IL1Rα lower than cutoff identified were significantly associated with a shorter DFS. In the multivariate analysis, high IP10 was confirmed as negatively associated with OS (HR = 3.097, p = 0.014) and IL4 and TNFα remain negatively (HR = 2.75, p = 0.002) and positively (HR = 0.224, p = 0.049) associated with DFS, respectively. Simultaneous expression of low IL4 and high TNFα identified patients with best prognosis (HR = 0.313, p < 0.0001). In conclusion, we demonstrated that, among a series of cytokines, IL4 is the most significant independent prognostic factor for DFS in resectable PDAC patients, and it could be useful to select patients with high risk of early recurrence who may avoid an unnecessary resection.